2020
DOI: 10.1007/s40820-020-00521-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanohollow Carbon for Rechargeable Batteries: Ongoing Progresses and Challenges

Abstract: Among the various morphologies of carbon-based materials, hollow carbon nanostructures are of particular interest for energy storage. They have been widely investigated as electrode materials in different types of rechargeable batteries, owing to their high surface areas in association with the high surface-to-volume ratios, controllable pores and pore size distribution, high electrical conductivity, and excellent chemical and mechanical stability, which are beneficial for providing active sites, accelerating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 212 publications
(236 reference statements)
0
28
0
Order By: Relevance
“…149 Under the same overcharging condition, the hard carbon surface was found to contain less deposited lithium metal than the graphite surface, and the deposited lithium on the hard carbon surface is more likely to dissolve during the discharge process. 160,191 This may be related to a completely disordered hard carbon structure with only a small amount of stacked graphite sheets, but hard carbon also has the problem of low Coulombic efficiency in the first cycle. Therefore, it was proposed that hard carbon can be mixed with graphite to slow down lithium dendrite generation.…”
Section: Working Conditions Reasonsmentioning
confidence: 99%
“…149 Under the same overcharging condition, the hard carbon surface was found to contain less deposited lithium metal than the graphite surface, and the deposited lithium on the hard carbon surface is more likely to dissolve during the discharge process. 160,191 This may be related to a completely disordered hard carbon structure with only a small amount of stacked graphite sheets, but hard carbon also has the problem of low Coulombic efficiency in the first cycle. Therefore, it was proposed that hard carbon can be mixed with graphite to slow down lithium dendrite generation.…”
Section: Working Conditions Reasonsmentioning
confidence: 99%
“…Deconvoluted C1s spectrum shows (Fig. 2a) sp 2 41,42 Figure 2b shows the fitted N1s spectrum with four peaks at 398.77, 400.30, 401.58, and 402.76 eV corresponding to pyridnic-N, pyrrolic-N, graphitic-N, and oxide forms of nitrogen, respectively. 41,43 Notably, the presence of pyridinic-N, pyrrolic-N, and graphitic-N indicates doping of nitrogen in the graphitic carbon skeleton of PSCN.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…1 Carbon, in different forms, continues to be the dominant electrode material for both of these applications. 2 Particularly, recent research has shown that morphology tailored hierarchically porous nanostructures can yield considerably enhanced electrochemical properties. 1,3,4 This is so because of the existence of abundant macropores that facilitates mass transport by improving the wettability of the electrode/electrolyte interfaces thereby shortening the diffusion pathways for the charged species and the presence of micro-and/or mesopores that provides a high surface area desired for increased reaction sites.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, lithium-ion batteries with the liquid electrolytes possess many disadvantages, such as the electrolyte leakage, low safety, low energy density (<300 Wh•kg -1 ), these disadvantages seriously impede the further development of the rechargeable lithium secondary batteries [1][2][3][4][5][6][7][8]. Fortunately, ASSLMBs with solid-state electrolytes (SSEs) can solve the problems mentioned above perfectly, because the SSEs have several distinct advantages than the flammable liquid electrolytes, such as high thermal stability, high chemical/electrochemical stability and excellent mechanical properties [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%